2011
DOI: 10.1002/jor.21330
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor and protease expression during different phases of healing after rabbit deep flexor tendon repair

Abstract: The purpose of the study was to contribute to the mapping of molecular events during flexor tendon healing, in particular the growth factors insulin-like growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF) and nerve growth factor (NGF), matrix metalloproteinases (MMP-3 and MMP-13) and their inhibitors (tissue inhibitors of metalloproteinases, TIMP-1 and TIMP-3, and the protease cathepsin K. In a rabbit model of flexor tendon injury, the mRNA expression for the growth factors, MMPs and TIMPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
(58 reference statements)
1
26
1
Order By: Relevance
“…The influence of intrinsic VEGF expression during tendon healing on biomechanical properties of the degenerated tendon could be shown in the presented rat model. HIF-1/VEGF-induced angiogenesis not only supports tissue repair and remodeling of the injured tendon, 27 but also impairs its biomechanical stability by degradation of the extracellular matrix during endothelial invasion. 28 Secretion of MMPs facilitates capillary growth by matrix degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of intrinsic VEGF expression during tendon healing on biomechanical properties of the degenerated tendon could be shown in the presented rat model. HIF-1/VEGF-induced angiogenesis not only supports tissue repair and remodeling of the injured tendon, 27 but also impairs its biomechanical stability by degradation of the extracellular matrix during endothelial invasion. 28 Secretion of MMPs facilitates capillary growth by matrix degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that compared MMP levels during healing course of deep flexor tendon in rabbits, a 9-fold increase was observed in levels of MMP-3, and 30-fold increase in levels of MMP-13 after injury. While levels of MMP-13 remained high during the study period of 42 days, levels of MMP-3 returned to pre-injury levels at week 1 [14]. Based on these results, Berglund et al [14] indicated that MMP-3 is involved in early healing process while MMP-13 plays a role in remodeling.…”
Section: Discussionmentioning
confidence: 93%
“…While levels of MMP-13 remained high during the study period of 42 days, levels of MMP-3 returned to pre-injury levels at week 1 [14]. Based on these results, Berglund et al [14] indicated that MMP-3 is involved in early healing process while MMP-13 plays a role in remodeling. In the present study, levels of MMP-13 were similar in control groups who were not treated with the drug while they tended to gradually decrease in study groups towards the sixth week.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, several animal studies have demonstrated up-regulation of the IGF-1 expression during tendon healing [6,7,9]. This up-regulation was seen both during an early and a later phase of healing.…”
Section: Introductionmentioning
confidence: 87%